Strengthening National Character through Literacy: STPHBK and Kayuh Literasi Collaboration - Yudha Aviratri; Abdul Wahab Nafiyan (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Low literacy levels in communities contribute to broader social issues, including school dropout rates, limited workforce skills, and intergenerational poverty. Strengthening family-based literacy is essential to support character development and improve quality of life. Aims: This community service program aims to enhance literacy awareness among parents, improve the capacity of Taman Bacaan Masyarakat (TBM) tutors, and foster children’s literacy skills as a foundation for character building. Methods: This program employed a community development approach with an empowerment strategy, involving collaboration between lecturers, students, and the Kayuh Literasi community. The implementation consisted of three stages: (1) raising parents’ awareness through seminars and literacy workshops, (2) mentoring TBM tutors in designing engaging and leveled literacy activities, and (3) assessing children’s literacy skills using leveled reading books. Data were collected through observation and program documentation and analyzed descriptively. Result: The results indicate an improvement in parents’ understanding of their role in supporting literacy at home, increased creativity and competence of tutors in developing literacy activities, and positive changes in children’s reading motivation and abilities. The program also demonstrated the effectiveness of collaborative efforts between higher education institutions, literacy communities, and families in promoting literacy culture. Conclusion: The implementation of a community-based literacy program through a community development and empowerment approach effectively strengthens literacy awareness and practices among families and communities. This program offers a sustainable and replicable model for fostering literacy culture and character development.